Futures of ageing and technology – comparing different actors' prospective views. Issue 2 (4th May 2017) - Bechtold, Ulrike; Capari, Leo; Gudowsky, Niklas
ABSTRACT: Ambient and assistive technologies (AT) have the potential to increase individual autonomy, social participation and quality of life for ageing populations. In seeking to implement these technologies, national and supranational funding schemes have strongly supported primarily market-driven research activities. This means that other societally relevant aspects, such as specific social and cultural contexts, are likely to be underestimated if not neglected. In view of the development of RI, this would be a serious misconception. We examine three recent participatory forward-looking technology assessment studies that involved experts, stakeholders and laypersons in discussions about the future of ageing and AT, and identify the diverse futures they imagine. We show different ways an ageing society of the future can be pictured, and contribute to the discourse on European demographic change as a Grand Challenge. In the light of RI, this diversity of imagined futures underlines the finding that answers to societal challenges connected to an ageing population cannot only be found by means of technological solutions, societal aspects will also play an important role.